Traces of Islam Nusantara on the Tuban Coast: The Role of Kambang Putih Port and the Formation of Local Civilization - Azyura Nuraliya Kartika; Muhammad Alvian; M. Shifa Thohari; Muhammad Zuhrul Anam; Nurul Hakim (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the role of Kambang Putih Port in the process of spreading Islam and its contribution to the formation of local civilization in the coastal area of Tuban. This study is motivated by the strategic position of the coastal area as a main route for maritime trade interactions, which not only brought economic commodities but also cultural and religious values. The research method used is a qualitative approach with a descriptive type, through historical and sociological approaches. Data were obtained from literature studies, observations, documentation, and interviews with community leaders, and then analyzed using an interactive analysis model with triangulation techniques to ensure the validity of the data. The results of the study show that Kambang Putih Port has an important role as a trading center as well as a social interaction space that brings together various cultural groups. Through trading activities, Islamic values were gradually introduced by Muslim traders and reinforced by the role of religious scholars through a cultural da'wah approach. The Islamization process occurred peacefully, adaptively, and contextually, allowing it to integrate with local culture without causing conflict. This interaction gave rise to a form of cultural acculturation reflected in the socio-religious practices of the community, such as tahlilan, yasinan, and community-based activities. Furthermore, this study found that the presence of the port contributed to shaping the social structure, patterns of community life, and the spatial planning of the coastal area. The port functions as an agent of social change, promoting the development of an open, adaptive, and cosmopolitan society. Thus, the local civilization in Tuban is the result of the integration between economic activities, Islamic values, and local culture that developed sustainably. This study concludes that Kambang Putih Port not only serves as a trading center but also as a space for social and civilizational transformation. These findings reinforce the understanding that the process of Islamization in the Nusantara was more influenced by trade networks and social interactions than by political power.